Economic and environmental value stream map (E2VSM) simulation for multi-product manufacturing systems. Issue 6 (1st November 2016) - Alvandi, S.; Li, W.; Schönemann, M.; Kara, S.; Herrmann, C.
Abstract: Value stream mapping (VSM) is a well-accepted tool within lean manufacturing concept which is often used for analysing and designing the flow of materials and information required to manufacture a product. However, the analysis is static and single product oriented, which fails to cope with either the variation of production plan or a multi-product environment. In addition, the environmental impact of a manufacturing system is highly associated with the dynamic consumption of energy and resources. Despite the recent integration of VSM with simulation or environmental studies (in the domain of energy efficiency), still neglected is the dynamic assessment of all the resources involved in a multi-product production environment. This paper presents a methodology for modelling multi-product manufacturing systems with dynamic material, energy and information flows with the aim to generate economic and environmental value stream maps (E 2 VSM). The proposed methodology is validated with an industrial case.